PENGARUH KECUKUPAN MODAL, RISIKO PEMBIAYAAN, EFISIENI OPERASIONAL DAN LIKUIDITAS TERHADAP PROFITABILITAS (Studi Pada Bank Syariah dan Bank Konvensional di Indonesia) - Erma Setiawati; Dimas Ilham Nur Rois; Indah Nur Aini (Riset Akuntansi dan Keuangan Indonesia, 2017)
AbstractThe competition between conventional and Islamic banks is quite strict, this becomes a common trend because the banks want to attract and maintain the relation with their costumer, each bank must try and work hard to show their optimal financial performances.This research aims to find out the effect of capital adequacy, financing risk, operational efficiency and liquidity on the profitability of Islamic banks and Conventional banks, as well as to analyze the differences effect of capital adequacy, financing risk, operational efficiency and liquidity on profitability in Islamic banks and conventional banks in Indonesia. Population in this research are all Islamic bank and a conventional bank that listed in Indonesian bank (Bank Indonesia) on 2011-2015. This research using purposive sampling technique, with the samples involving three Islamic bank and four conventional banks in Indonesia. The data is analyzed by multiple regression analysis and descriptive analysis. The result of this research shows that the capital adequacy and operational efficiency has a significant effect on the profitability of Islamic banks. The financing risk and liquidity have no significant effect on the profitability of Islamic banks. While the capital adequacy, operational efficiency, and liquidity have a significant effect on their profitability conventional banks, and the financing risk is not affected to conventional banks profitability. The result of this research also showed that there's a difference in the effect of capital adequacy, financing risk, operational efficiency and liquidity on profitability between Islamic banks and Conventional Bank. Keywords: capital adequacy, financing risk, operational efficiency, liquidity and profitability